PENDAMPINGAN AKUNTANSI DASAR UNTUK PENGUATAN TATA KELOLA KOPERASI MERAH PUTIH DI DESA BULOTALANGI KECAMATAN BULANGO TIMUR KABUPATEN BONE BOLANGO - Lukum, Amir; Mahdalena, Mahdalena; Bokiu, Zulkifli (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2025)
Cooperatives play a strategic role as drivers of the village economy, but they still face many challenges in financial governance. This community service program aims to provide basic accounting guidance to the management of the Merah Putih Cooperative in Bulotalangi Village, East Bulango District, Bone Bolango Regency, to strengthen governance from its inception. The implementation method included initial observation, training and workshops, transaction recording practice, and evaluation through pre- and post-tests. The program was attended by 12 participants, consisting of cooperative management, village officials, and community members. The evaluation results showed a significant increase in understanding of basic accounting, with an average pre-test score of 4.2 increasing to 8.1 in the post-test. Furthermore, this activity also raised awareness of the importance of accountability and transparency in financial reporting as the foundation for cooperative sustainability. Overall, this mentoring program was able to improve financial literacy while strengthening professional and sustainable cooperative governance. Keywords: Mentoring, Basic Accounting, Cooperative, Governance, Bulotalangi Village